A folkloristic analysis of Polish immigrant narratives in Western Canada - Deutsch, James (My University, 2020)
The large wave of Polish immigration to Canada during the years immediately following World War II also brought the production of written narratives that reflect upon the process of migration and settlement in the new place. Although these migrants included persons from all across Poland, of different age groups, backgrounds, and occupations, the migration narratives share certain distinctive formulas and patterns, particularly in terms of their plot lines and narrative structure. Each story highlights the journey and its difficulties, the arrival and culture shock, the struggle to adapt, and finally acceptance of life in the new world. This article focuses on the migration experiences of Józef Bauer (arriving in Canada in 1946), Helena Beznowska (arriving 1948), Marian Pawiński (arriving 1949), and Erika Wolf-May (arriving 1953). Explored from a folkloristic perspective, these four narratives fulfill the four functions of folklore: entertainment, education, validation and reinforcement of beliefs and conduct, and maintaining the stability, solidarity, cohesiveness, and continuity of a group within the larger mass culture. Moreover, as folkloric expressions of culture, the narratives not only reflect our very human culture, but also reinforce our shared humanity.
Keywords: Canada; folklore; immigration/migration; life writing; Poland; World War II